2014
DOI: 10.1136/bcr-2013-200212
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse malignant epithelioid mesothelioma in a background of benign multicystic peritoneal mesothelioma: a case report and review of the literature

Abstract: Peritoneal mesotheliomas are unusual entities with diverse origins and outcomes. Both benign and malignant variants exist. Benign multicystic peritoneal mesotheliomas (BMPMs), also known as multiple or multilocular peritoneal inclusion cysts, are extremely rare tumours arising from the peritoneal mesothelium covering the abdominal serous cavity. Even though these entities are considered benign tumours, BMPMs tend to recur after surgical resection, and in two cases have been reported to undergo malignant transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…2,6 Article Some authors considered it to be a mesothelial neoplasm because it may recur locally and in rare cases may show malignant transformation. 4,9 In the present study, Case 1 had diffuse involvement of peritoneal surface by the cystic tumors and pushing invasion into mesentery. Case 6 recurred 3 years and 11 months after complete cytoreduction, and histologic findings showed invasion of small cysts into subcutaneous tissue of umbilicus.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…2,6 Article Some authors considered it to be a mesothelial neoplasm because it may recur locally and in rare cases may show malignant transformation. 4,9 In the present study, Case 1 had diffuse involvement of peritoneal surface by the cystic tumors and pushing invasion into mesentery. Case 6 recurred 3 years and 11 months after complete cytoreduction, and histologic findings showed invasion of small cysts into subcutaneous tissue of umbilicus.…”
Section: Discussionmentioning
confidence: 49%
“…Accordingly, MCPM may be composed of two subtypes: i.e. diffuse type (Case 1, 6) and localized type with borderline malignant potential (Case 2, 3,4,5,7,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…We could only find 3 case reports of malignant transformation (González-Moreno et al, 2002;Mino et al, 2014;Sethna et al, 2003), one of which showed both benign and malignant cells within the same tumor, questioning whether the patient really had benign cystic mesothelioma which transformed, or a primary malignant process. Therefore, we see little added value of radical surgery with HIPEC in terms of prevention of malignant transformation.…”
Section: Resultsmentioning
confidence: 99%
“…Though incidental malignant transformation has been reported (González-Moreno et al, 2002;Mino et al, 2014), the survival rate is high, with the risk and comorbidity of surgery itself being a prominent factor, due to the radicalness of the procedure, extensive wound surface and postoperative adhesion formation. Sequela like infertility and induced menopause can be further complications.…”
Section: Introductionmentioning
confidence: 99%
“…BCM is considered a benign condition with only a few reported deaths 7 8. The aetiology is unknown; it is unclear if the lesion is a true neoplastic process or a reactive condition.…”
Section: Discussionmentioning
confidence: 99%